Functional (un-)Coupling: Impairment, Compensation, and Future Progression in Alzheimer's Disease. (May 2023) - Mosbacher, Jochen A.; Waser, Markus; Garn, Heinrich; Seiler, Stephan; Coronel, Carmina; Dal-Bianco, Peter; Benke, Thomas; Deistler, Manfred; Ransmayr, Gerhard; Mayer, Florian; Sanin, Guenter; Lechner, Anita; et al.
Background: Functional (un-)coupling (task-related change of functional connectivity) between different sites of the brain is a mechanism of general importance for cognitive processes. In Alzheimer's disease (AD), prior research identified diminished cortical connectivity as a hallmark of the disease. However, little is known about the relation between the amount of functional (un-)coupling and cognitive performance and decline in AD.Method: Cognitive performance (based on CERAD-Plus scores) and electroencephalogram (EEG)-based functional (un-)coupling measures (connectivity changes from rest to a Face-Name-Encoding task) were assessed in 135 AD patients (age: M  = 73.8 years; SD  = 9.0). Of these, 68 patients ( M  = 73.9 years; SD  = 8.9) participated in a follow-up assessment of their cognitive performance 1.5 years later.Results: The amounts of functional (un-)coupling in left anterior-posterior and homotopic interhemispheric connections in beta1-band were related to cognitive performance at baseline (β = .340; p  < .001; β = .274; P  = .001, respectively). For both markers, a higher amount of functional coupling was associated with better cognitive performance. Both markers also were significant predictors for cognitive decline. However, while patients with greater functional coupling in left anterior-posterior connections declined less in cognitive performance (β = .329; P  = .035) those with greater functional coupling in interhemispheric connections declined more (β = −.402; P  = .010).Conclusion: These findings suggest an important role of functional coupling mechanisms in left anterior–posterior and interhemispheric connections in AD. Especially the complex relationship with cognitive decline in AD patients might be an interesting aspect for future studies.